(3OjhGf GdTgGH GdMLGRjs - (3TgGH GdOjf CMeO eMeO Hf Ydj GdCfUGQj GdNRQLj,J (B875 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3agPg ofHPI ef TYQj, hbWYI EbJWYJgG ef fKQj, CdJeSgG efj ef dG CSJWjY gd QOG, hdG CLO ef WGYJg HOGhGbJQM Ydqj Cf CQJHgG Ydi GdSHYI afhf GdeTghQI s
(3BNQgG (B:s
(3aCLGH QMeg Gddg, GdMeO ddg hGgH GdYGajI, jSJMb ef SdN gPG GdebWhY Cf jbWY hjSJhLH ef QVi HfSHI gPjf GdHjJjf Edjg Cf jUaY adh QBg GdUaOj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B219s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B135 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQHGd (B(475) s
Keywords: (3GdCOHs